A Review on Current Research on H3 and H4 Receptors - Chaurasiya, Vicky; Bhoir, Vivek; Bhundere, Soniya; Chauhan, Yashwant; Chavan, Kusum; Shriram, Bairagi; Smita, Takarkhede (Asian Journal of Pharmaceutical Research and Development, 2023)
This review article provides an overview of the structure, location, and functional uses of H3 and H4 histamine receptors. It examines the current research on the topic, including the structure of the receptors, their location in the body, and their role in the body’s response to histamine. It also looks at potential, therapeutic applications of these receptors and their potential to be used as drug targets. The article concludes with a discussion of potential future directions for research on these receptors. The identification of Histamine (H3) & (H4) receptors .Some years ago relined interest in histamine research and exposed attracting perspectives for the potential therapeutic exploitation & these new drug targets. While the H3 receptors is mainly localized in the CNS, the of the brain and the morphologic characterization histamine producing neurons proved the existence of histaminergic system in the mammalian brain, It is primarily expressed in hematopoietic cell, indicating their function in neurotransmission and immunomodulation, respectively. Although structural similarities between H3 and H4 & Species difference in their pharmacological profiles are causes of limitation in their evaluation & their biological profile the development of selective ligands for there receptors. The H3 and H4 is recognised drug target for neuronal diseases, such as Cognitive Disorder, Neuropathic pain and Sleep Wake Disorder considering the topicality & this area of research. This review focuses on the pharmacology of selected promising indication and the rationalefor the application of H3and H4 ligands.